RANKING ALTERNATIVES USING PIPRECIA METHOD: A CASE OF HOTELS’ WEBSITE EVALUATION - Stanujkic, Dragisa; Karabasevic, Darjan; Popovic, Gabrijela (Journal of process management and new technologies, 2021)
The article presents the application of the PIvot Pairwise RElative Criteria Importance Assessment (PIRECIA) method for ranking alternatives. The PIPRECIA method is primarily intended for determining the significance (weight) of criteria, but it can also be used for completely solving decision-making problems. So far, this method has not been used for completely solving multiple criteria decision-making problems, which is why this article presents the application of the PIPRECIA method for the evaluation and ranking alternatives. The process of evaluating alternatives using the PIPRECIA method is shown on an example of evaluating the websites of some hotels located in Southern and Eastern Serbia.
Keywords: PIPRECIA; Evaluacija web sajta